1972
DOI: 10.3382/ps.0511460
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Egg Shell Thickness Measurements Using Ultrasonic Energy

Abstract: Non-destructive thickness measurements have been made on Brown Pelican and chicken egg shells using ultrasonic thickness measurement techniques. Excellent agreement with the standard dial gage micrometer method is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Although neither the frequencies, intensity, couplant media nor the operating temperatures were stated in the report by Gould (1972), the frequency and intensities used in nondestructive testing units are similar to those employed in this study. Therefore, the use of this type of treatment, especially if the frequency is 2 MHz.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Although neither the frequencies, intensity, couplant media nor the operating temperatures were stated in the report by Gould (1972), the frequency and intensities used in nondestructive testing units are similar to those employed in this study. Therefore, the use of this type of treatment, especially if the frequency is 2 MHz.…”
Section: Resultsmentioning
confidence: 84%
“…Gould (1972) reported on uses of ultrasonic energy as a means of measuring egg shell thickness. None of the above reported on the effect of ultrasound on fertile or incubating eggs, although Gould (1972) mentioned this as a possible factor of concern.…”
Section: Introduction T He Use Of Ultrasonic Energy As a Methodsmentioning
confidence: 99%
“…A recent technique to measure eggshell thickness is the use of ultrasonic energy (Gould, 1972). A high degree of accuracy is claimed.…”
Section: Thicknessmentioning
confidence: 99%
“…28 -30 It has been suggested that ultrasound could be used in nondestructive measurement of the thickness of egg shells. 31 The most informative experiments in the embryonated chick egg were performed because of its value as a basic biologic test system. Brettschneider3 2 was unable to produce developmental abnormalities by exposing chick eggs to 1 to 3 W/cm 2 intensities through an intact shell.…”
Section: Studies In Aviansmentioning
confidence: 99%